PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA PENFUI TIMUR KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Meliani Helena Suryanti Netha; Maria Douk Tunti (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
This research aims to determine the Application Of Good Governance Principles In Managing Village Fund Allocation In East Penfui Village, Central Kupang Sub-District, Kupang Regency. The data used in this research is qualitative data with primary data sources and secondary data. The data collection technique in this research is triangulation with data analysis methods using the analytical model used by Miles and Huberman. The results of this study indicate that the Application Of The Principles Of Good Governance In The Management Of Village Fund Allocation In East Penfui Village, Central Kupang Sub-District, Kupang Regency is in accordance with the principles of good governance, that is: professionality, accountability, transparency, excellent service, democracy and participation, efficiency and effectiveness, rule of law and can be accepted by the whole society. In realizing the Principles Of Good Governance In The Management Of Village Fund Allocation, East Penfui Village, apparatus always hold deliberations on the management of village fund allocation to the community.